KEANEKARAGAMAN JENIS IKAN DI SUNGAI BATANG GADIS MANDAILING NATAL SUMATERA UTARA - Yusni Atifah; Fitri Agustina Lubis (Scripta Biologica, 2017)
Batang Gadis River, located in Mandailing Natal, faces a severe threat by the increase of human activities along the river. The fish community, as well as other biotas, is exposed to reducing environmental condition. Therefore, the study of fish community in this river is essential to get the most recent condition as a baseline data. The purpose of this research was to determine the species diversity of fish in Batang Gadis River of Mandailing Natal. This research used a descriptive exploratory method by surveying with purposive sampling method to collect samples at four specified stations. This study used a fishing net with a zig-zag pattern of sampling covered the river bank for about 200–300m at each observation station. The collected fish samples were identified at the Biology Laboratory of the University of Muhammadiyah Tapanuli Selatan. This study found ten species of fish from five families. The family with the most significant members was Cyprinidae (6 species), and the other families, Bagridae, Clariidae, Nemachelidae, and Loricariidae, were found with only one species. The species diversity comprised of Rasbora lateristriata, Nemacheilus fasciatus, Mystacoleucus marginatus, Tor tambra, Cyprinus carpio, Clarias bathracus, Rasbora argyrotaenia , Barbonymus gonionotus, Puntius binotatus, Bagrus nemurus, and Pterygoplichthys pardalis. The fish population of Batang Gadis River has diversity index (H’) of 1.77 and similarity index (E) of 0.77.